Combining LC-MS/MS profiles with network pharmacology to predict molecular mechanisms of the hyperlipidemic activity of Lagenaria siceraria stand. (10th January 2023) - Banerjee, Subhadip; Tiwari, Amrendra; Kar, Amit; Chanda, Joydeb; Biswas, Sayan; Ulrich-Merzenich, Gudrun; Mukherjee, Pulok K.
Abstract: Ethnopharmacological relevance: Lagenaria siceraria Stand. (Family: Cucurbitaceae), popularly known as bottle gourd, is traditionally used in Ayurvedic medicine as a food plant, especially in hypertension and obesity. Aim of the study: Investigations were undertaken to assign novel lead combinations from this common food plant to multi-molecular modes of actions in the complex disease networks of obesity and hypertension. LC–MS/MS based metabolite screening, in-vivo high fat diet induced hyperlipidemia animal study and network pharmacology explorations of the mechanism of action for lipid lowering effects including a neighbourhood community approach for molecular combinations were performed. Material and methods: Major chemical constituents of the fruits of LS (LSFE) were analysed by HPLC-DAD-MS/MS-QTOF. Wistar albino rats (n = 36), divided into 6 groups (n = 6) received either no treatment or a high-fat diet along with LSFE or Atorvastatin. Lipid profiles and biochemical parameters were evaluated. In silico cross-validated network analyses using different databases and Cytospace were applied. Results: Profiling of LSFE revealed 18 major constituents: phenolic acids like p-Coumaric acid and Ferulic acid, the monolignolconferyl alcohol, the flavonoid glycosides hesperidin and apigenin-7-glucoside. Hyperlipidemic animals treated with LSFE (200 mg/kg, 400 mg/kg, 600 mg/kg) showed a significant improvement of their lipid profiles after 30 days of treatment. Network pharmacology analyses for the major 18 compounds revealed enrichment of the insulin and the ErbB signalling pathway. Novel target node combinations (e.g. AKR1C1, AGXT) including their connection to different pathways were identified in silico . Conclusions: The combined in vivo and bioinformatics analyses propose that lead compounds of LSFE act in combination on relevant targets of hyperlipidemia. Perturbations of the IRS→Akt→Foxo1 cascade are predicted which suggest further clinical investigation towards development of safe natural alternative to manage hyperlipidemia. Graphical abstract: Image 1 Highlights: The ethanolic fruit extract of Lagneria sicereria reduces hyperlipidemia in rats. Extract profiling by HPLC-DAD-MS/MS-QTOF revealed 18 major constituents. Network pharmacology analyses predict involvement of insulin and ErbB signalling. Combined in vivo and network pharmacology analyses on relevant targets related to hyperlipidemia.